PENERAPAN BIOFILTRASI MODULAR ADSORBEN ALAMI UNTUK PENGOLAHAN LIMBAH CAIR BATIK DI DESA WONOSARI - Bayyinah, Nur; Adinugroho, M Ludy; Cahyani, Amanda Dea; A, Devani Afiyatul; Kirana, Kartika Candra; Mustika, M. Choirul; W, Putri Nurdiana; Handayani, Dwining; Baihaqi, Ahmad Fist Cal; S, Arsy Aisyah Malika R.; Saputra, M. Adi; Cahyani, Gita Ayu; Hibatullah, Rizaldi Naufal (Department of Agronomy, Faculty of Agriculture, University of Jember, 2025)
Wastewater pollution from the batik industry has become a serious environmental issue, particularly at the level of Micro, Small, and Medium Enterprises (MSMEs) that generally lack access to proper waste treatment technologies. Wonosari Village, located in Gondang Wetan Subdistrict, Pasuruan Regency, is one of the batik centers facing similar challenges, where untreated wastewater potentially contaminates the surrounding environment. This community service program through KKN-UMD Universitas Jember was carried out to provide an alternative solution by implementing the Biofiltration Modular with Natural Adsorbent (BIMA) system. The method involved field observation, the design of a BIMA prototype using layered filter media (gravel, sand, coconut fiber, activated carbon, cotton, and TiO2), as well as socialization and training for batik MSME actors and local communities. The results demonstrated that BIMA was effective in improving the visual characteristics of batik wastewater, indicated by reduced dark color, decreased turbidity, and the elimination of unpleasant odors. In addition, the program enhanced community awareness and participation in environmental management. In conclusion, the application of BIMA through the KKN program not only offers a simple, affordable, and adaptable technical solution but also strengthens community empowerment and fosters sustainability through village institutional support and digital promotion as a branding tool for Wonosari Village.